A study on laparoscopic appendectomy at emergency theatre in B. P. Koirala Institute of Health Sciences - Mandal, Subhash Chandra; Aryal, Shiva Sharma; Adhikary, Shailesh (International Surgery Journal, 2021)
Background: Laparoscopic appendectomy is gaining its popularity as it has better patient compliance. Despite of not being “gold standard”, laparoscopic appendectomy is widely practiced in emergency setting and has become patient’s as well as surgeon’s choice of treatment. Our aim is to acknowledge the advantage and importance of laparoscopic appendectomy at emergency in a retrospective study. Our main objective was to study the efficacy of laparoscopic appendectomy, patients’ demographic profile as well as conversion rate of laparoscopic appendectomy to open appendectomy. Methods: This hospital based retrospective study was carried among 54 patients who had undergone emergency laparoscopic appendectomy at B. P. Koirala Institute of Health Sciences (BPKIHS) between March and April, 2016. The patient’s file was collected from medical record section, studied and analyzed. Results: During the study, it was observed that most of the patients were female (62.97%) and the patients were mostly between 20 to 40 years of age (Mean age 27 years±10.88 SD). Most of the patients presented within 24 hours of onset of symptoms, most commonly with pain in lower abdomen associated mostly with vomiting. Out of 54 patients, 48 patients (88.89%) were diagnosed with acute appendicitis. Frankly speaking, laparoscopic appendectomy was associated with shorter hospital stay (around 3 days) and also has less conversion rate (11.11%). There were minimal post-operative complications without any case of redo and mortality. Conclusions: Laparoscopic appendectomy is safe and efficient procedure with shorter hospital stay and less post-operative complication.